PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA WORKSHOP SMK KATOLIK SANTO MIKAEL SURAKARTA - Indriyani, Etty; Haryanto Petrus C, Wisnu (STIE AUB Surakarta)
This aims of this study is to determine the influence of Organizational Culture and Job Satisfaction on Employee Performance with Organizational Commitment As an intervening variable in vocational Workshop Catholic Saint Michael Surakarta. From the research on this study population, which are the entire staffs of the St. Michael's Catholic Vocational Workshop Surakarta as many as 33 peoples. In can be concluded that the organizational culture, job satisfaction has a positive significant effect on performance, while organizational commitment is influenced by job satisfaction and organizational commitment have a positive and significant impact on performance as explained by the total value of R square of 98%, the variable in the Employee Performance Workshop SMK Catholic Mikael Surakarta saint, explained variations bell Organizational Culture and Job Satisfaction with the commitment as an intervening variable by 98% while the remaining 2% is explained by other variables outside the model. Also concluded that the total impact of Organizational Culture on the performance effect of 0.271 is smaller than the total effect of job satisfaction on performance of 0.702. So as to improve performance more effectively through an increase job satisfaction